Development of nanobodies against Mal de Río Cuarto virus major viroplasm protein P9‑1 for diagnostic sandwich ELISA and immunodetection - Llauger, Gabriela (2021)
Mal de Río Cuarto virus (MRCV) is a member of the genus Fijivirus of the family Reoviridae that causes a devastating disease in maize and is persistently and propagatively transmitted by planthopper vectors. Virus replication and assembly occur within viroplasms formed by viral and host proteins. This work describes the isolation and characterization of llama-derived Nanobodies (Nbs) recognizing the major viral viroplasm component, P9-1. Specific Nbs were selected against recombinant P9-1, with affinities in the nanomolar range as measured by surface plasmon resonance. Three selected Nbs were fused to alkaline phosphatase and eGFP to develop a sandwich ELISA test which showed a high diagnostic sensitivity (99.12%, 95% CI 95.21–99.98) and specificity (100%, 95% CI 96.31–100) and a detection limit of 0.236 ng/ml. Interestingly, these Nanobodies recognized different P9-1 conformations and were successfully employed to detect P9-1 in pull-down assays of infected maize extracts. Finally, we demonstrated that fusions of the Nbs to eGFP and RFP allowed the immunodetection of virus present in phloem cells of leaf thin sections. The Nbs developed in this work will aid the study of MRCV epidemiology, assist maize breeding programs, and be valuable tools to boost fundamental research on viroplasm structure and maturation.